Russian Integration with Belarus Is the Supertask: Interview with Anatolii Evgen'evich Lokot'. Issue 6 (2nd June 2016) - Unknown
Abstract : The current relationship between Russia and Belarus is the most successful example of integration in the interests of both states among the post-Soviet countries. Despite the Union State's somewhat amorphous nature, our countries' rapprochement in the various areas of economics, politics, culture, and management has not stalled. In this article, A.E. Lokot', mayor of Novosibirsk, former State Duma deputy and member of the Union State parliament responds to questions from EKO.